ODPOWIEDZIALNOŚĆ UCZESTNIKÓW KORPORACYJNYCH ORGANIZACJI KOMERCYJNYCH W PRAWIE ROSYJSKIM - Moskwa, Leopold; Rovnyy, Valery V. (Wydział Prawa i Administracji UAM, 2009)
A comprehensive analysis o f the liability of members of the Russian Federation of commercial corporate organisations for the obligations of those organisations requires focusing on three sets of rules: 1) the basic rules which usually determine the issue of the liability of the members of a given commercial organisation for its obligations, 2) the rules that deal with the liability o f members within the frames of the contributions that have not been actually made, 3) the rules that pertain to the liability of parent companies for the obligations of their daughter companies. Without a shadow o f a doubt, the first set of rules is of a primary character. Relying on the main of those rules, one may conclude that the liability of partners in general partnerships and members of limited liability companies and joint-stock companies is rather standardised - partners in general partnerships have unlimited liability, i.e. are liable with their all property, for the obligations of a partnership, while shareholders are not at all liable for the obligations o f companies. It is interesting to note that in a limited partnership, general partners are liable for the obligations of a partnership pursuant to the same rules as partners in general partnerships. Specific rules do not determine, however, the issue of liability of the limited partners. In connection therewith - based on the general rule - one should conclude that limited partners are not liable for the obligations of a partnership and, hence, the creditors of the latter may not direct their claims towards the personal estate of the limited partners. A rather unique situation exists in companies with supplementary liability and producer’s co-operatives, the participants of which (members or partners) are liable for the obligations of the organisation in a limited manner: in companies with supplementary liability - up to the level determined in the incorporation documents, which is based on the multiplication o f the contributions made, and in the producer’s co-operatives - up to the level determined in the Act on the Producer’s Co-operatives and in the statutes of a given co-operative.
LIABILITY OF THE MEMBERS OF COMMERCIAL CORPORATE ORGANISATIONS UNDER RUSSIAN LAW